2005
DOI: 10.1152/ajpheart.00625.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental oxygen administration on coronary blood flow in patients undergoing cardiac catheterization

Abstract: Patients with heart disease are frequently treated with supplemental oxygen. Although oxygen can exhibit vasoactive properties in many vascular beds, its effects on the coronary circulation have not been fully characterized. To examine whether supplemental oxygen administration affects coronary blood flow (CBF) in a clinical setting, we measured in 18 patients with stable coronary heart disease the effects of breathing 100% oxygen by face mask for 15 min on CBF (via coronary Doppler flow wire), conduit coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 38 publications
(42 reference statements)
6
116
1
2
Order By: Relevance
“…In 1969 Bourassa et al [33] reported from experimental studies that high flow oxygen can reduce coronary blood flow sufficiently to worsen outcomes. More recently McNulty et al [34] provided evidence that high flow oxygen reduces coronary artery blood flow and confirmed the previously evidence base. Yet the practice of using high flow oxygen persisted and was endorsed for years, and despite subsequent changes in guidelines [1,12], there is evidence that the ritual still persists [35].…”
Section: The Danger Of Oxygen During Emergency Therapysupporting
confidence: 57%
“…In 1969 Bourassa et al [33] reported from experimental studies that high flow oxygen can reduce coronary blood flow sufficiently to worsen outcomes. More recently McNulty et al [34] provided evidence that high flow oxygen reduces coronary artery blood flow and confirmed the previously evidence base. Yet the practice of using high flow oxygen persisted and was endorsed for years, and despite subsequent changes in guidelines [1,12], there is evidence that the ritual still persists [35].…”
Section: The Danger Of Oxygen During Emergency Therapysupporting
confidence: 57%
“…In the lung it has been observed decreased mucociliar transport, inflammatory reaction, focal pulmonary edema, interstitial fibrosis and reabsorption atelectasis. In the cardiocirculatory system, higher oxygen tension decreases cardiac output and stroke volume with increased peripheral vascular resistances and coronary artery vasoconstriction (66)(67)(68)(69). The peripheral vasoconstriction, in particular, may explain the possible gap between high PaO 2 and low tissue oxygen tension.…”
Section: * * * Luciano Gattinonimentioning
confidence: 99%
“…[99][100][101] Kilgannon et al 63 have demonstrated that hyperoxia played a greater role in mortality than did hypoxia following cardiac arrest. A number of other investigations and meta-analyses 102-107 on this subject have been published following the work of Kilgannon.…”
Section: Myocardial Infarction/cardiac Arrestmentioning
confidence: 99%